2011
DOI: 10.1093/jxb/err055
|View full text |Cite
|
Sign up to set email alerts
|

Genetic dissection of vitamin E biosynthesis in tomato

Abstract: Vegetables are critical for human health as they are a source of multiple vitamins including vitamin E (VTE). In plants, the synthesis of VTE compounds, tocopherol and tocotrienol, derives from precursors of the shikimate and methylerythritol phosphate pathways. Quantitative trait loci (QTL) for α-tocopherol content in ripe fruit have previously been determined in an Solanum pennellii tomato introgression line population. In this work, variations of tocopherol isoforms (α, β, γ, and δ) in ripe fruits of these … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
75
0
3

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 73 publications
(88 citation statements)
references
References 98 publications
(107 reference statements)
4
75
0
3
Order By: Relevance
“…19 Tocopherol quantification by high-performance liquid chromatography. Tocopherol extraction and quantification was performed exactly as previously described 9 . Briefly, tomato fruits were ground to a fine powder in liquid nitrogen and 500 mg of material was extracted with 1.5 ml methanol and, after vortex mixing, 1 ml chloroform was added.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…19 Tocopherol quantification by high-performance liquid chromatography. Tocopherol extraction and quantification was performed exactly as previously described 9 . Briefly, tomato fruits were ground to a fine powder in liquid nitrogen and 500 mg of material was extracted with 1.5 ml methanol and, after vortex mixing, 1 ml chloroform was added.…”
Section: Methodsmentioning
confidence: 99%
“…While g-and a-tocopherol are produced by the sequential activities of dimethyl-phytylquinol methyl transferase (VTE3, EC 2.1.1.-), tocopherol cyclase (VTE1, EC 5.3.-.-) and tocopherol C-methyl transferase (VTE4, EC 2.1.1.95); d-and b-tocopherol synthesis, do not require VTE3 activity being formed merely by the action of the latter two enzymes (Fig. 1a) 9 . The role of tocopherols as lipid-soluble antioxidants is well documented for plants and humans and occurs by two mechanisms: (i) donation of a hydrogen atom to a highly reactive polyunsaturated fatty acid peroxyl radical thus preventing a chain reaction of lipid peroxidation and (ii) physically or chemically quenching singlet oxygen species, which damage many biological molecules including proteins, DNA, carbohydrates and polyunsaturated fatty acids 10 .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…7, 8). The structure of these two types of compounds is very similar; but, while tocopherols have a saturated phytol tail, tocotrienols possess an isoprenoid tail with three unsaturated residues (Das et al 2007;Almeida et al 2011). Tocopherols and tocotrienols biosynthesis takes place in the chloroplasts from the aromatic ring of the homogentisic acid.…”
Section: Tocopherols and Tocotrienols Biosynthesismentioning
confidence: 99%
“…It has been shown that tocopherols present in seed can be converted nearly completely to a-tocopherol by engineering increased expression of the two pathway methyl transferases, VTE3 and VTE4 (Van Eenennaam et al, 2003), and, in another study, manipulation of four VTE genes, singly and in combination, was shown to impact both tocopherol composition and total content (Karunanandaa et al, 2005). Several groups have identified QTL explaining the variance of seed vitamin E composition and content in biallelic populations of Arabidopsis (Gilliland et al, 2006), sunflower (Helianthus annuus; Hass et al, 2006), maize (Chander et al, 2008), and the fruit of tomato (Schauer et al, 2006;Almeida et al, 2011). For many of these studies, vitamin E biosynthetic genes colocalized to some of the QTL intervals, but the size of the QTL intervals had limited definitive demonstration of the molecular basis of the QTL and, thus, whether they are due to modifications of biosynthetic gene function or expression.…”
Section: Vitamin E (Tocopherol)mentioning
confidence: 99%